The relationship between tinnitus characteristics, stress and depression in patients with subjective tinnitus - Luengrungrus, Kittiphorn; Wannasri, Arnat (Journal of Associated Medical Sciences, 2025)
Background: Tinnitus is a perception of a noise in the ears. Individuals with tinnitus symptoms may experience disrupt daily life activities and mental health issues such as stress and depression. Objectives: This study aimed to examine the relationship between the tinnitus symptoms and mental health conditions – stress and depression – in individuals with subjective tinnitus. Materials and methods: This was an analytical cross-sectional study, involved 139 participants with subjective tinnitus aged between 18 and 70 years. All participants underwent clinical hearing tests. The tinnitus severity level was assessed by the Tinnitus Handicap Inventory in Thai version (THI), while the Stress Test 5 (ST-5) and the nine-question depression screening test (9Q) were used to assess stress and depression, respectively. Results: After adjusting for tinnitus-related variables, the overall THI scores showed significantly positively associated with both the ST-5 and 9Q scores. Additionally, gender was also significantly positively associated with the 9Q scores. In contrast, other tinnitus-related factors including age, affected ear, tinnitus pattern and duration and average hearing thresholds in the affected ear, showed no statistically significant correlations with the ST-5 and 9Q scores. Conclusion: This study highlights a significant association between the THI scores and both ST-5 and 9Q, indicating that tinnitus severity is closely linked to the development of stress and depression. Therefore, it is essential to monitor and manage psychological distress in patients with tinnitus.